The effect of Accounting Profit and Cash Flow Operations on Stock Returns (Empirical Study on Mining Companies Coal listed on the Indonesia Stock Exchange for the period 2016-2020) - Fenni Yufantria; Selvi Safelia (TECHNOBIZ : International Journal of Business, 2022)
This study aims to determine the effect of Accounting Profit and Cash Flow Operations on Stock Returns (Empirical Study on Mining Companies Coal listed on the Indonesia Stock Exchange for the period 2016-2020) both in terms of partial or simultaneous. This research is a type of quantitative research. Population in This research is a coal mining company listed on the Stock Exchange Indonesian Effect. The sample was determined by purposive sampling technique and obtained by 28 companies. The data in this study are secondary data which obtained from the Indonesia Stock Exchange (IDX). Data analysis method used in this study include descriptive statistics, classical assumption test, analysis test multiple regression, test of determination R2, t test (partial) and f test (simultaneous). The results of the study show that: (1) Accounting Profit is not significant effect on Stock Return, with t-count value -0.702 < t-table- 1,669 (2) Operating Cash Flow has a positive and significant effect on Return Shares, with t-count 2.541 > t-table 1.669 (3) Accounting Profit and Cash Flow Operations together have a significant effect on Stock Return, with f-count 3,229 > 3,138 f-table.Keywords: Accounting Profit, Operating Cash Flow and Stock Return.